The Influence Of Price Discounts, Product Bundling, Brand Collaboration On Purchasing Decisions At The Es Teh Indonesia Bandar Kediri Branch - Arum Oktaviani, Sekar; Ambarwati , Diana (RISK : Jurnal Riset Bisnis dan Ekonomi, 2024)
The increase in consumer spending is driving Indonesia's economic growth. The culinary industry has emerged as a solution to meet the needs of the community. The culinary industry is rapidly growing, leading to intense business competition. Es Teh Indonesia Bandar Kediri is one of the culinary companies in Kediri that is making efforts to face business competition by using promotional strategies such as price discounts, product bundling, and brand collaboration to attract buyer interest, increase sales, and expand market reach. This research uses a quantitative research method. The population is the consumers of Es Teh Indonesia in Bandar Kediri, with a sample size of 385 respondents. Non-probability sampling research method, accidental sampling technique, questionnaire sample collection technique. Techniques for analysis include validity testing, reliability testing, classical assumption testing, multiple linear regression testing, t-testing, f-testing, and coefficient of determination testing. Based on the research findings, it is concluded that price discounts have a significant impact on purchasing decisions, product bundling does not have a significant effect, and brand collaboration has a significant influence. All three variables significantly influence the purchasing decision